Government Roles in Maintaining Public Order, Krian: Peran Pemerintah dalam Memelihara Ketertiban Umum, Krian - Muchorrotun, Siti; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2025)
General background: Local government apparatus, including Satpol PP, is central to enforcing local regulations and maintaining community order. Specific background: In Krian District, innovations such as the Public Order Report Management Information System (SIMLITABMAS) accompany conventional enforcement roles. Knowledge gap: The balance between regulatory enforcement, community participation, coordination with police/TNI, and public perceptions remains uncertain. Aims: This qualitative study describes and analyzes government roles as dinamisator, regulator, katalisator, and fasilitator in organizing public order and community tranquility. Results: Findings indicate regulator, catalyst, and facilitator roles are generally effective; the dinamisator role (mobilizing community proactivity) is less effective, and coordination and enforcement challenges persist (e.g., handling illegal structures, pollution complaints). Novelty: The study documents district-level digital reporting innovation (SIMLITABMAS) alongside institutional-role analysis. Implications: Improving multi-agency coordination, community engagement strategies, and clearer SOPs can strengthen Satpol PP performance while addressing public trust and enforcement consistency.